Isolation of Human Xenospecific Regulatory T Cells with High Suppressive Function. (July 2018) - Noyan, Fatih; Zimmermann, Katharina; Hardtke-Wolenski, Matthias; Mederacke, Young-Seon; Tenspolde, Michel; Petersen, Bjoern; Niemann, Heiner; Huehn, Jochen; Manns, Michael; Jaeckel, Elmar
Abstract : Organ shortage is currently the biggest hurdle in the successful treatment of patients with organ failure. Xenotransplantation, using porcine cells, tissues and organs may be one of the ways to avoid the growing organ shortage. CD4+CD25highFOXP3+ regulatory T cells (Tregs) are involved in graft-specific tolerance after solid organ transplantation and in xenotransplantation. While polyspecific Tregs can prevent immune responses under lymphopenic conditions, antigen-specific Tregs are needed to treat autoimmunity and graft rejection. Yet reliable markers for these cells are missing. Methods: We investigated various activation markers on regulatory T cells after activation with porcine PBMCs for the potential to isolate xenospecific nTregs. Results: We report that latency associated peptide (LAP) and glycoprotein A repetitions predominant (GARP) can identify xenospecific Tregs after activation. In addition, we show that the depletion of CD154+ cells from LAP+ or GARP+ Tregs increases the Treg purity to over 90% as assessed by epigenetic analysis. These xenospecific Tregs can be isolated magnetically and might allow the development of GMP based protocols. In addition, they were functionally far superior to CD4+CD25high or CD4+CD25highCD127low Tregs in xenospecific mixed lymphocyte reactions in vitro. Furthermore, xenospecific LAP+CD154- nTregs could completely prevent rejection of porcine skin in immune reconstituted humanized NRG mice in the absence of any immunosuppression (operational tolerance). and in preventing strong alloreactions in humanized mice. Conclusion: Xenospecific LAP+CD154- nTregs could therefore have a high therapeutic potential to control even strong xenospecific immune responses after transplantation.